Determination of optimal harvest boundaries for 'Ambrosia' apple fruit using a delta-absorbance meter. Issue 3 (3rd May 2016) - DeLong, John M.; Harrison, Peter A.; Harkness, Lisa
ABSTRACT: In this study, a new chlorophyll measurement tool, the delta absorbance (DA) meter, was used to develop an optimal harvest maturity model for 'Ambrosia' apple ( Malus × domestica Borkh.) fruit. Fruit from four commercial orchards in the Annapolis Valley, Nova Scotia, Canada, were sampled (25 fruit from three or four trees per location) over nine consecutive weekly harvests during the 2011 and 2012 growing seasons, and 8 weeks in the 2013 season. At each harvest, five fruit from each orchard site had their index of absorbance difference ( I AD ) values, firmness, mass, titratable acidity (TA), soluble solids content (SSC), red skin colouration and internal core ethylene concentrations measured. Following approx. 3 months of storage at 3.5°C, 20 fruit from each site were removed and assessed for the incidence of disorders such as senescent breakdown, cortical browning and coreflush. Chlorophyll concentrations in the epidermis were strongly and positively related to I AD values in the same tissue ( P ≤ 0.001), confirming the assumption that chlorophyll was the basis for the DA meter I AD signal. In addition, I AD values declined significantly during fruit maturity and were negatively related to harvest week ( P ≤ 0.001). The optimum harvest period was identified by aligning all 'at harvest' I AD values, fruit quality measurements, and 'post-storage' disorder data with the corresponding harvest week. I AD values associated with harvests having the highest commercial fruit quality then delineated the optimal harvest boundaries. The upper boundary I AD value of 0.47 was defined as 'when to begin harvest', while the lower boundary I AD value of 0.28 was considered to be 'when to end harvest' for long-term storage. The use of a DA meter and its I AD value to define the optimal harvest boundaries may be applicable to all commercial apple cultivars, but should be developed for each cultivar and growing region.